Penerjemahan Klausa Transitif Dari Bahasa Arab ke Dalam Bahasa Indonesia - Farid Ma’ruf; Taufik Akhmad; Ahmad Edwar (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
The objective of this research was to obtain an overall view of translation of transitive clause from Arabic to Indonesian. This study used a qualitative approaching using a content analysis methode. The data used in this study is Arabic transitive clause including its translation procedures and its translation accuracy into Indonesian. The data source in this study is Himar Al-Hakim novel by Taufik Al-Hakim chapter 1-3 and its translation on Indonesia ‘Keledai yang Bijak’ translated by Harits Fadly.The results of this study indicate that the transitive clause of Arabic uses a standard clause 1 pattern (Verb[S] - Object) which is 79%. When viewed from the grammatical structure, the translation of the transitive clauses of Arabic in Indonesian is not always a transitive clause. In certain cases, transitive clauses can be translated into intransitive clauses, passive clauses, non-verbal clauses and even translated into phrases.There are nine procedures used by translators: literal procedures, modulation, transposition, cultural equivalence, functional equivalence, naturalization, recognized-translation, transference and deletion. In general, it can be said that most of the translations are accurate translations, although there are also eight inaccurate translations because there is a deviation of the meaning and omission of the meaning caused by the author's mistake in choosing the equivalent word and the failure of the author in understanding the source text.